Dosis facit effectum: Why the scope of the carbon tax matters - Evidence from the Swedish residential sector - Petrik Runst; Anita Thonipara (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2019)
Sweden has gradually increased its carbon tax within the past 25 years and imposes the world's highest tax on carbon dioxide emissions today. This paper examines the impact of the Swedish carbon tax on residential carbon emissions as well as on consumer behavior. We perform Difference-in-Differences (DiD) regressions and Synthetic Control Methods (SCM) in order to evaluate the causal impact of carbon taxation on carbon emissions in the residential sector. Both methods provide evidence for a causal effect of the carbon tax augmentation in the early 2000s on residential carbon emissions. We find that the scope of the reduction of residential carbon emissions due to the carbon tax augmentation range between 200kg (when compared to other countries with a carbon tax of more than 20 Euros implemented) and 800 kg of CO2 per capita per year (when compared to countries without a carbon tax). Hence, the evidence points towards the effectiveness of carbon taxation in reducing residential CO2 emissions and, thus, mitigating climate change.
Keywords: Q54; P28; Q4; O38; 330; carbon tax; Sweden; residential building; CO2 emissions